Analisis Penerapan Good Manufacturing Practice (GMP) di CV. Buana Citra Sentosa, Yogyakarta - Nur Itsna Kurniasari; Silvia Oktavia Nur Yudiastuti; Ricky Jadi Rezeqi (JOFE : Journal of Food Engineering, 2022)
GMP application is used to support the industry to be responsible for the products produced. In addition, by implementing GMP, the competitiveness of the industry will increase. The application analysis of the GMP in CV. Buana Citra Sentosa aims to provide solutions caused by GMP deviations in the industry. The method used in analyzing the GMP application is the scoring method with the AHP (Analytical Hierarchy Process) method approach. The results of the evaluation can be used to determine the compatibility of GMP implementation. Based on the GMP feasibility level assessment, CV. Buana Citra Sentosa was at a satisfactory level and was declared eligible.Total GMP assessment score in CV. Buana Citra Sentosa is 493 which means it is close to the requirements of the Good Processed Food Production Method.